Function of astrocyte MyD88 in high-fat-diet-induced hypothalamic inflammation - Sungho Jin; Kwang Kon Kim; Byong Seo Park; Dong Hee Kim; Bora Jeong; Dasol Kang; Tae Hwan Lee; Jeong Woo Park; Jae Geun Kim; Byung Ju Lee (Journal of Neuroinflammation, 2020)
Abstract Background A growing body of evidence shows that hypothalamic inflammation is an important factor in the initiation of obesity. In particular, reactive gliosis accompanied by inflammatory responses in the hypothalamus are pivotal cellular events that elicit metabolic abnormalities. In this study, we examined whether MyD88 signaling in hypothalamic astrocytes controls reactive gliosis and inflammatory responses, thereby contributing to the pathogenesis of obesity. Methods To analyze the role of astrocyte MyD88 in obesity pathogenesis, we used astrocyte-specific Myd88 knockout (KO) mice fed a high-fat diet (HFD) for 16 weeks or injected with saturated free fatty acids. Astrocyte-specific gene expression in the hypothalamus was determined using real-time PCR with mRNA purified by the Ribo-Tag system. Immunohistochemistry was used to detect the expression of glial fibrillary acidic protein, ionized calcium-binding adaptor molecule 1, phosphorylated signal transducer and activator of transcription 3, and α-melanocyte-stimulating hormone in the hypothalamus. Animals’ energy expenditure was measured using an indirect calorimetry system. Results The astrocyte-specific Myd88 KO mice displayed ameliorated hypothalamic reactive gliosis and inflammation induced by injections of saturated free fatty acids and a long-term HFD. Accordingly, the KO mice were resistant to long-term HFD-induced obesity and showed an improvement in HFD-induced leptin resistance. Conclusions These results suggest that MyD88 in hypothalamic astrocytes is a critical molecular unit for obesity pathogenesis that acts by mediating HFD signals for reactive gliosis and inflammation.